Comparative Study for Alignment of Extramedullary Guides versus Portable, Accelerometer-Based Navigation in Total Knee Arthroplasty - Matsumoto, Kazu; Ogawa, Hiroyasu; Fukuta, Masashi; Mori, Nobuyuki; Akiyama, Haruhiko (The Journal of Knee Surgery, 2018)
The use of portable, accelerometer-based navigation (PN) devices for positioning of the components of total knee arthroplasty (TKA) is emerging as an alternative to standard extramedullary (EM) systems, which was needed to the image intensifier. The aim of our study was to compare the accuracy of component positioning in TKA using an EM and PN systems. Data from 100 consecutive primary TKAs, performed by multiple surgeons in 87 patients between October 2010 and June 2015, were analyzed. Coronal and sagittal plane alignments of the TKA components, relative to the mechanical axis of the limb, were evaluated by radiography. The mean postoperative coronal alignment angle of the femoral (α) and tibial (β) components was comparable between the groups (α: PN, 89.9 ± 2.2 degrees; EM, 89.9 ± 1.6 degrees and β: PN, 90.1 ± 1.4 degrees; EM, 89.6 ± 1.3 degrees). Groups were also comparable with regard to mean postoperative sagittal alignment angle of the femoral and tibial components (γ: PN, 2.3 ± 3.3 degrees; EM, 1.8 ± 1.7 degrees and σ: PN, 89.7 ± 2.5 degrees; EM, 90.1 ± 1.3 degrees). The incidence rate of a component malalignment > 3 degrees in the coronal and sagittal planes of the mechanical axis of the knee was comparable between the groups. In conclusion, the coronal and sagittal alignments for the femoral components was less accurate compared with tibial component alignment, especially in the PN group, and the sagittal alignment of the femoral component was less accurate than coronal alignment for both groups. Both the PN and EM systems provide satisfactory coronal and sagittal component alignments in TKA. Further technical improvement of the PN system could further improve its application for accurate component implantation in TKAs.
Keywords: total knee arthroplasty; extramedullary guides; portable navigation; coronal alignment; sagittal alignment